Inkuiri Terbimbing untuk Meningkatkan Berpikir Kritis dan Kemandirian Belajar pada Materi Trigonometri Lanjut - Wibowo, Harris Adi; Waluya, Budi; Rosyida, Isnaini (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2025)
This study aims to develop and evaluate the effectiveness of a mathematics learning module based on inquiry guided learning in advanced trigonometry to enhance students' critical thinking skills and learning independence at the high school level. The research employed a research and development approach involving two Grade XI science classes at SMA Santa Maria Cirebon. The module was developed through a series of stages including needs analysis, design, expert validation, and classroom implementation over the course of one month. Data were collected through learning outcome tests, observations, and interviews, and analyzed using both quantitative and qualitative methods. The results show that the module effectively improved students' academic performance, with most students demonstrating increased scores and enhanced critical thinking skills. The findings also indicate a positive correlation between learning independence and exam scores. However, some students still struggled due to low levels of independent learning. Instrument validation confirmed that the test items met criteria for content validity, alignment with curriculum indicators, and the ability to assess higher-order thinking skills. This study concludes that the inquiry guided learning approach is effective in improving mathematics learning quality and highlights the importance of fostering independent learning as an integral part of the educational process.